Major QTLs associated with green stem disorder insensitivity of soybean (Glycine max (L.) Merr.) - Yamada, Tetsuya (Breeding science, 2014)
Green stem disorder (GSD) is one of the most serious syndromes affecting soybean (Glycine max) cultivation in Japan. In GSD, stems remain green even when pods mature. When soybean plants develop GSD, seed surfaces are soiled by tissue fluid and seed quality is deteriorated during machine harvesting. We performed quantitative trait locus (QTL) analyses for GSD insensitivity using recombinant inbred lines (RILs; n = 154) derived from a cross between an insensitive line ('Touhoku 129') and a sensitive leading cultivar ('Tachinagaha') during a 6-year evaluation. Three effective QTLs were detected. The influences of these QTLs were in the following order: qGSD1 (LG_H) > qGSD2 (LG_F) > qGSD3 (LG_L). At these three QTLs, 'Touhoku 129' genotypes exhibited more GSD insensitivity than 'Tachinagaha' genotypes. The lower incidence of GSD for 'Touhoku129' was attributable primarily to these three QTLs because RILs harboring a 'Touhoku 129' genotype at the three QTLs exhibited a GSD incidence similar to that of 'Touhoku 129.' Although a limitation of this study is that only one mapping population was evaluated, this QTL information and the flanking markers of these QTLs would be effective tools for resolving GSD in soybean breeding programs